Extracellular ATP induces cell death in human intestinal epithelial cells - Souza, Carolina O.; Santoro, Giani F.; Figliuolo, Vanessa R.; Nanini, Hayandra Ferreira; de Souza, Heitor S.P.; Castelo-Branco, Morgana Teixeira Lima; Abalo, Alessandra Alves; Paiva, Mauricio M.; Coutinho, Claudia M.L.M.; Coutinho-Silva, Robson (Biochimica et biophysica acta, 2012)
Extracellular ATP is an endogenous signaling molecule released by various cell types and under different stimuli. High concentrations of ATP released into the extracellular medium activate the P2X7 receptor in most inflammatory conditions. Here, we seek to characterize the effects of ATP in human intestinal epithelial cells and to evaluate morphological changes in these cells in the presence of ATP. We treated human intestinal epithelial cells with ATP and evaluated the effects of this nucleotide by scanning and transmission electron microscopy analysis and calcium measurements. We used flow cytometry to evaluate apoptosis. We collected human intestinal explants for immunohistochemistry, apoptosis by the TUNEL approach and caspase-3 activity using flow cytometry analyses. We also evaluated the ROS production by flow cytometry and NO secretion by the Griess technique. ATP treatment induced changes characteristic of cell death by apoptosis and autophagy but not necrosis in the HCT8 cell line. ATP induced apoptosis in human intestinal explants that showed TUNEL-positive cells in the epithelium and in the lamina propria. The explants exhibited a significant increase of caspase-3 activity when the colonic epithelial cells were incubated with IFN-gamma followed by ATP as compared to control cells. In addition, it was found that antioxidants were able to inhibit both the ROS production and the apoptosis induced by ATP in epithelial cells. The activation of P2X7 receptors by ATP induces apoptosis and autophagy in human epithelial cells, possibly via ROS production, and this effect might have implications for gut inflammatory conditions. ► Extracellular ATP induces apoptosis and autophagy in human intestinal epithelial cells. ► Extracellular ATP induces caspase-3 activation and apoptosis in explants of human gut epithelial tissue from health donors. ► Inflammatory condition can increase the ATP effects in human intestinal epithelial cells.